IMMEDIATE PARTIAL DENTURE PROSTHESIS - A CASE REPORT - Bhat, Vinaya; Balaji, S. Sriram (Journal of Health and Allied Sciences NU, 2013)
Prosthodontic management of a patient who requires immediate denture needs lot of understanding from the operator. Immediate dentures must be compatible both biologically and physiologically with the oral environment. Also the co operation exhibited by the patient towards the treatment protocol also plays a major role in its success. This case report describes a patient treated with immediate partial denture prosthesis.
Keywords: Immediate partial denture; Immediate tooth replacement